2015
DOI: 10.1038/onc.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

The BET bromodomain inhibitor JQ1 suppresses growth of pancreatic ductal adenocarcinoma in patient-derived xenograft models

Abstract: The primary aim of this study was to evaluate the antitumor efficacy of the bromodomain inhibitor JQ1 in pancreatic ductal adenocarcinoma (PDAC) patient-derived xenograft (tumorgraft) models. A secondary aim of the study was to evaluate whether JQ1 decreases expression of the oncogene c-Myc in PDAC tumors, as has been reported for other tumor types. We used five PDAC tumorgraft models that retain specific characteristics of tumors of origin to evaluate the antitumor efficacy of JQ1. Tumor-bearing mice were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
112
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 66 publications
(63 reference statements)
8
112
2
Order By: Relevance
“…Since BET inhibitors significantly decrease collagen I expression by primary cancer-associated PSCs, our results suggest that JQ1 may also block PDAC progression indirectly by decreasing collagen I-rich ECM deposition. Importantly, JQ1 can also directly limit growth of PDAC cells in vitro in patient-derived xenograft models and in transgenic mouse models (19,21,22,34). Our findings that JQ1 decreases ADM development in the EL-Kras G12D mouse model in vivo are in agreement with the report showing that JQ1 decreases ADM in ex vivo acinar cultures and in the PdxCre/LSL-Kras (KC) mouse model (21).…”
Section: Discussionsupporting
confidence: 82%
“…Since BET inhibitors significantly decrease collagen I expression by primary cancer-associated PSCs, our results suggest that JQ1 may also block PDAC progression indirectly by decreasing collagen I-rich ECM deposition. Importantly, JQ1 can also directly limit growth of PDAC cells in vitro in patient-derived xenograft models and in transgenic mouse models (19,21,22,34). Our findings that JQ1 decreases ADM development in the EL-Kras G12D mouse model in vivo are in agreement with the report showing that JQ1 decreases ADM in ex vivo acinar cultures and in the PdxCre/LSL-Kras (KC) mouse model (21).…”
Section: Discussionsupporting
confidence: 82%
“…Although MYC mRNA levels were slightly decreased upon the treatment with JQ1 in vivo, no regulation of MYC protein expression was described (54). In contrast, expression of the cell-cycle regulator CDC25B (cell division cycle 25B) was diminished, and this molecular event closely correlated with therapeutic efficacy (54), arguing that CDC25B is the relevant BET-I-sensitive driver in the investigated model. In addition to the human PdX models, JQ1 activity was recently demonstrated in a genetically engineered PDAC mouse model (GEMM).…”
Section: Targeting Myc Indirectlymentioning
confidence: 98%
“…In human PDAC patient-derived xenotransplants (PdX), JQ1 showed activity (54). It was demonstrated that JQ1 reduced proliferation and a distinct reduction in tumor growth in 4 of 5 individual subcutaneous PdX models (54). Although MYC mRNA levels were slightly decreased upon the treatment with JQ1 in vivo, no regulation of MYC protein expression was described (54).…”
Section: Targeting Myc Indirectlymentioning
confidence: 99%
See 2 more Smart Citations